Pearl Harbor: First Hand Accounts of December 7, 1941 - Brown, William H. (My University, 2010)
On the morning of December 7, 1941, the naval and aerial forces of the Japanese Empire secretly attacked the United States Navy at the naval base of Pearl Harbor, Hawaii. For over two hours, two waves consisting of over three hundred Japanese aircraft destroyed the Pacific Fleet of the United States Navy. Every ship along Battleship Row either took significant damage or sank during those early morning hours. Thousands of sailors in the United States Navy witnessed in horror as the Japanese bombed and destroyed their ships.
Winner: Rhem-Schwarzmann Prize awarded by Joyner Library 2011.
Keywords: Pearl Harbor (Hawaii); Japanese empire; War; United States. Navy--Pacific Fleet; Eye witnesses